2021
DOI: 10.3390/ani11092550
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota, Anti-Inflammatory, and Anti-Oxidative Status of Broiler Chickens Fed Diets Containing Mushroom Waste Compost By-Products

Abstract: This study investigated the effects of using mushroom waste compost as the residue medium for Pleurotus eryngii planting, which was used as a feed replacement; its consequent influence on broiler chickens’ intestinal microbiota, anti-inflammatory responses, and anti-oxidative status was likewise studied. A total of 240 male broilers were used and allocated to four treatment groups: the basal diet—control group (corn–soybean); 5% replacement of a soybean meal via PWMC (Pennisetum purpureum Schum No. 2 waste mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…In order to better understand the connection between intestinal barrier and gut microflora, the cecum content which contains the most detailed information regarding chicken gut microbiota was analyzed with 16s rRNA methodology ( Pourabedin and Zhao, 2015 ). Similar to the previous reports ( Chuang et al., 2021b ), data from analyses of α-diversity and β-diversity corroborate the initial hypothesis that SCH improved microbial richness and altered microbiota structure to a certain extent. The diversity of the intestinal tract microbiota community is believed to have a positive effect on the productivity of the bird ( Janczyk et al, 2009 ).…”
Section: Discussionsupporting
confidence: 89%
“…In order to better understand the connection between intestinal barrier and gut microflora, the cecum content which contains the most detailed information regarding chicken gut microbiota was analyzed with 16s rRNA methodology ( Pourabedin and Zhao, 2015 ). Similar to the previous reports ( Chuang et al., 2021b ), data from analyses of α-diversity and β-diversity corroborate the initial hypothesis that SCH improved microbial richness and altered microbiota structure to a certain extent. The diversity of the intestinal tract microbiota community is believed to have a positive effect on the productivity of the bird ( Janczyk et al, 2009 ).…”
Section: Discussionsupporting
confidence: 89%
“…The enrichment of Faecalicoccus is usually associated with intestinal inflammation, including ulcerative colitis and Crohn’s disease ( 71 ). These results are consistent with previous findings that dietary-fiber-rich by-products could modulate the composition of the cecal microbiota of chickens ( 72 74 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it was found that lentinan sulfate polysaccharide can improve the multiple organ dysfunction syndrome induced by yeast polysaccharides in mice and reduce the vacuolization of mouse liver 46]. The improvement in liver morphology can be attributed to the bioactive compounds in mushrooms such as B vitamins, minerals, polysaccharides, lentinan and so on, which have the effect of liver protection and enhancing the antioxidant capacity of the liver [43,[46][47][48][49][50][51][52][53][54]. The present study showed that LEF can reduce hepatic MDA levels and enhance the ability of hepatocytes to remove hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%